LA TERMINOLOGIE GASTRONOMIQUE D’ORIGINE SLAVE EN ROUMAIN - POPUȘOI, Carolina (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Gastronomic Terminology of Slavic Origin in Romanian. This article aims to discuss some aspects concerning the gastronomic terminology of Slavic origin (from Old Slavic, Bulgarian, Ukrainian, Russian, Belarusian, Serbian, Polish), which penetrated into Romanian at different sociocultural stages. Our analysis takes as a basis the specialized lexicon excerpted in Dicționarul explicativ al limbii române (DEX) (“The Explanatory Dictionary of the Romanian Language”), Micul dicționar academic (MDA) (“The Little Academic Dictionary”), as well as the words excepted on the Internet (this type of lexicon being nowadays an unrivaled source of enrichment of a language with the borrowings from other languages). The terminological elements discussed here are grouped into two categories, according to the period of their penetration into the language, their methods of penetration, but also according to the place they currently occupy in specialized works (notably in dictionaries, scientific works). The novelty of this research consists above all in the identification and study of Slavic gastronomic borrowings recently penetrated into Romanian. Terminologia gastronomică de origine slavă în limba română. În acest articol, se pun în discuție o serie de aspecte legate de terminologia gastronomică de origine slavă (slava veche, bulgară, ucraineană, rusă, belorusă, sârbă, poloneză), care a pătruns în diverse etape socio-culturale în limba română. Analiza noastră are la bază lexicul de specialitate excerptat din Dicționarul explicativ al limbii române (DEX), Micul dicționar academic (MDA), precum și din mediul online (acesta fiind, în zilele noastre, o sursă inegalabilă de îmbogățire a unei limbi cu împrumuturi din alte limbi). Elementele terminologice abordate sunt grupate în două subclase, în funcție de perioada în care au pătruns în limbă, de modalitățile de intrare, dar și de locul pe care-l ocupă în momentul de față în lucrările de specialitate (dicționare, lucrări științifice). Noutatea acestei cercetări ține, în special, de semnalarea și abordarea împrumuturilor gastronomice slave intrate recent în limba română. Cuvinte-cheie: terminologie, gastronomie, contact lingvistic, împrumut, slavism. Article history: Received 29 September 2023; Revised 15 December 2023; Accepted 17 January 2024; Available online 27 March 2024; Available print 27 March 2024.